Quantification of 17 Endogenous and Exogenous Steroidal Hormones in Equine and Bovine Blood for Doping Control with UHPLC-MS/MS - Giovanni Caprioli; Michele Genangeli; Ahmed M. Mustafa; Riccardo Petrelli; Massimo Ricciutelli; Gianni Sagratini; Stefano Sartori; Fulvio Laus; Sauro Vittori; Manuela Cortese (MDPI AG, 2021)
A simple and fast analytical method able to simultaneously identify and quantify 17 endogenous and exogenous steroidal hormones was developed in bovine and equine blood using UHPLC-MS/MS. A total amount of 500 µL of sample was deproteinized with 500 µL of a mixture of methanol and zinc sulfate and evaporated. The mixture was reconstituted with 50 µL of a solution of 25% methanol and injected in the UHPLC-MS/MS triple quadrupole. The correlation coefficients of the calibration curves of the analyzed compounds were in the range of 0.9932-0.9999, and the limits of detection and quantification were in the range of 0.023-1.833 and 0.069-5.5 ppb, respectively. The developed method showed a high sensitivity and qualitative aspects allowing the detection and quantification of all steroids in equine and bovine blood. Moreover, the detection limit of testosterone (50 ppt) is half of the threshold admitted in plasma (100 ppt). Once validated, the method was used to quantify 17 steroid hormones in both bovine and equine blood samples. The primary endogenous compounds detected were corticosterone (range 0.28-0.60 ppb) and cortisol (range 0.44-10.00 ppb), followed by androstenedione, testosterone and 11-deoxycortisol.